Loss of soil by water erosion on production systems differents with potato Solanum tuberosum L. - Alvarado Narváez, Kevin; López Peñafiel, Vanessa; Castillo Franco, Jesús (Revista de Ciencias Agrícolas, 2011)
This research was developed in the FEDEPAPA’s experimental station located in Obonuco, a Pasto city town, Nariño State, which is 1°13" north and 77°16"west, an altitude of 2.710 meter above sea level, an annual average rain fall of 840mm and an average temperature of 13°C where it were tested the soil loss by water erosion in seven productive potato systems (Solanum tuberosum) with three replications in a complete block design in random in a ground between 31-42% slope; runoff plots were established with a channel for collecting soil and sediment for two tanks to determine the amount of loss soil in kg.ha-1 after each precipitation event, data were expressed in weight of dry soil and measurements were performed during a cycle potato crop. The experiment was installed on a land portion that remained for a period of 10 years under cover of kikuyo grass (Pennisetum clandestinum). The variance analysis showed significant differences between treatments, with greater soil losses for T2 (potato monoculture with mechanic tillage, chemical and organic fertilization); with an average of 450.17 kg.ha-1 and with less soil loss in the T4 treatment (potato crop with Brazilian grass barriers Phalaris sp mechanic tillage and chemical fertilization) with an average of 164.55 kg.ha-1, indicating the effectiveness of barriers in contour Phalaris sp as alternative for Soil Conservation in potato crops on the hillside area. Also measured soil loss by the human induced erosion in the job, obtaining values of 6120 kg.ha-1 soil losses equivalent to 0.15cm of arable layer soil.